The Effects of Professional Occupational Competence Deficiencies on the TVET Lecturers: A Case Study - Mulaudzi , Maelekanyo Christopher; Maluka, Mojalefa Daniel (Journal of Technical Education and Training, 2024)
The quality of TVET college lecturers significantly affects the development and performance of students and, as a consequence, the economy. This study utilises Wenger’s theory of social learning to explore the impact of professional occupational competence deficiencies on TVET lecturers at selected public colleges in Gauteng Province, South Africa. This study aimed to explore the effects of professional occupational competence deficiencies on the TVET lecturers across selected TVET colleges in the Gauteng Province, South Africa. Central to the challenge of lecturers professional occupational competence deficiencies is the lack of training and development to capacitate them with the necessary knowledge and skills to ensure that they play their roles optimally in providing students with quality education. A case study design was adopted in this study, underpinned by a qualitative research approach. A purposive sampling technique was used to select participants from five public TVET colleges in Gauteng Province. Data were collected from fifteen sampled participants through semi-structured interviews and processed through Atlas.ti. Thematic analysis technique was used to analyse the data. The findings of this study show that due to professional occupational competence deficiencies, TVET lecturers are experiencing profound challenges such as low self-efficacy, self-regulation failure, low motivation, anger, and resentment towards college management. To improve TVET lecturers’ competence, efforts need to be made to focus on teaching professional occupational competencies as a priority. This study outlines the challenges that professional occupational competence deficiencies pose for the TVET sector and, by implication, the national development imperatives of South Africa.